Positive electrode active material for lithium secondary battery, method for preparing same, and lithium secondary battery comprising same
The positive active substance of lithium secondary battery is prepared by directly using the leachate collected from waste batteries through the wet process, which solves the problems of complex process, high cost and poor battery performance in the prior art, and achieves simplified processes, reduced costs and environmental protection effects.
Patent Information
- Application Number
- CN202410713220.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-20
- Filing Date
- 2024-06-04
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art has problems such as complex process steps, high extraction cost, reduced purity and poor battery capacity and life performance in the preparation process of lithium secondary batteries.
The waste battery is processed through a wet process, and the positive electrode active material is prepared directly using the leachate recovered from the waste battery, without the need for additional solvent extraction steps, simplifying the process and reducing costs.
It has achieved simplified process, reduced cost and environmental protection effects, while improving the capacity retention rate and life stability of the positive electrode active material.
Smart Images

Figure CN119864387A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a preparation method thereof, and a lithium secondary battery comprising the positive electrode active material, and more particularly to preparing the positive electrode active material by using a leachate obtained by treating waste batteries through a wet process without an additional solvent extraction step. Background Art
[0002] Lithium secondary batteries are usually composed of a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, a separator and an electrolyte, and are charged and discharged by the intercalation-decalation of lithium ions. Lithium secondary batteries have the advantages of high energy density, large electromotive force and large capacity, so they are widely used in various fields.
[0003] At this time, the positive electrode active material of the lithium secondary battery contains precious metals such as nickel, manganese, and cobalt in addition to lithium. Since precious metals are relatively expensive metals, attempts have been made to recover these metals for reuse as raw materials.
[0004] Generally, for preparing the precursor of the positive electrode active material, it is necessary to use another extracting agent through multiple steps to sequentially extract the precious metals that are desired to be recovered from the waste battery, and then recover the extracted precious metals to prepare the precursor of the positive electrode active material again.
[0005] However, if precious metals are recovered by using extractants according to the type of metal, there are problems such as complicated process steps, increased extraction costs, and reduced purity, and it is not good from the perspective of environmental impact. In addition, when precious metals are extracted from the leachate of waste batteries to prepare positive electrode active material precursors, there is a problem that due to various impurities, the positive electrode active material prepared using pure metals exhibits poor performance in terms of battery capacity and life retention rate.
[0006] Prior art literature
[0007] Patent Document 1: KR10-2011-0122544B1 Summary of the invention
[0008] The object of the present invention is to provide an environmentally friendly positive electrode active material for lithium secondary batteries, a preparation method thereof, and a lithium secondary battery comprising the positive electrode active material, which does not require additional extraction steps and separation steps for each element for precious metals such as nickel, cobalt and manganese that are desired to be obtained from a leachate obtained through a waste battery recovery process, thereby simplifying the process and reducing the process cost.
[0009] The positive electrode active material according to one embodiment of the present invention may include:
[0010] a core portion containing a substance represented by the following chemical formula 1; and
[0011] a shell portion surrounding the core portion and containing a substance represented by the following chemical formula 2,
[0012] [Chemical formula 1]
[0013] Li(Ni a1 Mn b1 Co c1 ) 2
[0014] [Chemical formula 2]
[0015] Li(Ni a2 Mn b2 Co c2 )Me y O 2
[0016] In Chemical Formula 1 and Chemical Formula 2,
[0017] a1+b1+c1=1,
[0018] a2+b2+c2+y=1,
[0019] a1>a2,
[0020] Me is at least one metal selected from the group consisting of Na, Al, Fe, Cu, Zn, Mg, Ca, B, Zr, Nb, and combinations thereof.
[0021] In Chemical Formula 1, 0.8≤a1<1, and in Chemical Formula 2, 0<a2≤0.8 and 0.0001≤y≤0.05.
[0022] At the boundary between the core and the shell, nickel, cobalt and manganese may exist in a gradually changing concentration gradient.
[0023] The average particle size of the positive electrode active material may be 5 to 10 μm.
[0024] The average particle size of the core portion may be 4 to 8 μm, and the thickness of the shell portion may be 1 to 2 μm.
[0025] Me can come from the leachate of spent batteries.
[0026] The positive electrode active material can have a capacity retention rate of 91% or more after 80 cycles measured in a button half cell at 25° C. and an upper limit voltage of 4.3 V.
[0027] According to one embodiment of the present invention, a method for preparing a positive electrode active material is a method for preparing a positive electrode active material including a core portion and a shell portion, which may include: a first metal-containing solution preparation step, in which a first metal-containing solution is prepared to form a core portion; a recovery solution preparation step, in which a recovery solution containing nickel, cobalt and manganese recovered from waste batteries and having a composition different from that of the first metal-containing solution is prepared to form a shell portion; a core portion precursor formation step, in which a core portion precursor is formed using the prepared first metal-containing solution; a positive electrode active material precursor formation step, in which a shell portion precursor is formed on the surface of the core portion precursor using the recovery solution, thereby forming a positive electrode active material precursor; and a positive electrode active material formation step, in which a heat treatment is performed on the positive electrode active material precursor, thereby forming a positive electrode active material.
[0028] In the first metal-containing solution preparing step, the first metal-containing solution may contain 70 mol % or more and less than 100 mol % of nickel based on 100 mol % of the total metal elements contained in the first metal-containing solution.
[0029] In the recovery solution preparation step, the recovery solution may be prepared by mixing the leaching solution containing nickel, cobalt and manganese recovered from the waste battery and the second metal-containing solution containing nickel, cobalt and manganese.
[0030] The mixing ratio of the leachate and the second metal-containing solution may be 40 mol %:60 mol % to 80 mol %:20 mol %.
[0031] In the recovery solution preparation step, an alkaline solution may be mixed with the leachate to adjust the pH of the leachate to 5.5 or less.
[0032] In the core precursor forming step, an ammonia complexing agent and a basic compound may be added together with the prepared first metal-containing solution.
[0033] The positive electrode active material forming step may include a process of mixing a positive electrode active material precursor with a lithium-containing raw material and then sintering the mixture at 750 to 850° C. for 13 to 20 hours.
[0034] The method may further include washing the positive electrode active material precursor with water at a temperature of 5° C. or higher and lower than 10° C.
[0035] According to the present invention, the leachate obtained through the waste battery recycling process is used in the process of forming a positive active material precursor without undergoing a separate step of extracting precious metals and separating the elements.
[0036] Therefore, the process can be simplified and the process cost can be reduced. Furthermore, since the solvent used in the prior art for extracting nickel, cobalt and manganese does not need to be used, an environmental protection effect is produced.
[0037] In addition, due to the doping effect of impurities in the leaching solution on the positive electrode active material, it exhibits excellent capacity at high rates, and due to the low nickel content in the shell, the side reaction with the electrolyte can be minimized, thereby exhibiting stable life characteristics. In addition, due to the high manganese content in the shell, the thermal stability is improved, and a high life maintenance rate is exhibited at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a diagram showing the results of SEM analysis of the precursor particles prepared in Example 1 of the present invention.
[0039] Figure 2 The results of measuring the cross section of the precursor particles prepared in Example 1 of the present invention by energy dispersive spectroscopy are shown.
[0040] Figure 3 This is a diagram showing the results of SEM analysis of precursor particles prepared in Example 2 of the present invention.
[0041] Figure 4 The results of measuring the cross section of the precursor particles prepared in Example 2 of the present invention by energy dispersive spectroscopy are shown.
[0042] Figure 5 The diagram shows the results of SEM analysis of precursor particles prepared in Comparative Examples of the present invention.
[0043] Figure 6 The results of measuring the cross sections of precursor particles prepared in Comparative Examples of the present invention by energy dispersive spectroscopy are shown.
[0044] Figures 7 to 9 The results of charge and discharge tests and measurement of cycle characteristics of batteries using the positive electrode active materials prepared in Examples 1 and 2 of the present invention and the positive electrode active materials prepared in Comparative Examples are shown. DETAILED DESCRIPTION
[0045] Figure 1 This is a diagram showing the results of SEM analysis of the precursor particles prepared in Example 1 of the present invention. Figure 2 The results of measuring the cross section of the precursor particles prepared in Example 1 of the present invention by energy dispersive spectroscopy are shown. Figure 3 This is a diagram showing the results of SEM analysis of precursor particles prepared in Example 2 of the present invention. Figure 4 The results of measuring the cross section of the precursor particles prepared in Example 2 of the present invention by energy dispersive spectroscopy are shown. Figure 5 The diagram shows the results of SEM analysis of precursor particles prepared in Comparative Examples of the present invention. Figure 6 The results of measuring the cross sections of precursor particles prepared in Comparative Examples of the present invention by energy dispersive spectroscopy are shown. Figures 7 to 9The results of charge and discharge tests and measurement of cycle characteristics of batteries using the positive electrode active materials prepared in Examples 1 and 2 of the present invention and the positive electrode active materials prepared in Comparative Examples are shown.
[0046] Hereinafter, the embodiments disclosed in this specification will be described in detail with reference to the accompanying drawings. In this specification, the same or similar components are given the same reference numerals in any figure, and repeated description thereof is omitted.
[0047] When describing the embodiments disclosed in this specification, if it is determined that a detailed description of the related known technology may obscure the main idea of the embodiments disclosed in the present invention, the detailed description will be omitted. In addition, it should be understood that the drawings are only used to facilitate the understanding of the embodiments disclosed in this specification, and the technical ideas disclosed in this specification are not limited by the drawings, including the modified embodiments, equivalent embodiments and even alternative embodiments within the technical ideas and technical scope of the present invention.
[0048] The terms including serial numbers such as first, second, etc. are used to describe various components, but the components are not limited by the terms. The terms are used only to distinguish one component from another.
[0049] Unless the context clearly indicates a different meaning, an expression in the singular includes an expression in the plural.
[0050] In this specification, terms such as "including" or "having" are intended to indicate the existence of implementation features, values, steps, operations, constituent elements, parts or combinations thereof described in the specification, and should not be understood as excluding the existence of one or more other features, values, steps, operations, constituent elements, parts or combinations thereof or other possibilities in advance.
[0051] The positive active material according to the present invention may include: a core portion including a substance represented by the following Chemical Formula 1; and a shell portion surrounding the core portion and including a substance represented by the following Chemical Formula 2.
[0052] [Chemical formula 1]
[0053] Li(Ni a1 Mn b1 Co c1 ) 2
[0054] [Chemical formula 2]
[0055] Li(Ni a2 Mn b2 Co c2 )Me y O 2
[0056] In Chemical Formula 1 and Chemical Formula 2,
[0057] a1+b1+c1=1,
[0058] a2+b2+c2+y=1,
[0059] a1>a2,
[0060] Me is at least one metal selected from the group consisting of Na, Al, Fe, Cu, Zn, Mg, Ca, B, Zr, Nb, and combinations thereof.
[0061] First, the average particle size of the positive electrode active material may be 5 to 10 μm.
[0062] The average particle size of the core portion may be 4 to 8 μm.
[0063] The thickness of the shell portion may be 1 to 2 μm.
[0064] The volume of the shell portion may be 40 to 60 volume % based on 100 volume % of the total volume of the positive electrode active material including the core portion and the shell portion.
[0065] The average particle size of the positive electrode active material is relatively small, at 5 to 10 μm, and the shell is formed in a manner that occupies 40 to 60% of the volume. A concentration balance is formed during the sintering process, and nickel, cobalt and manganese can have a gradually changing concentration gradient at the boundary between the core and the shell.
[0066] More specifically, the concentration of nickel has a concentration gradient in which the core of the positive electrode active material particles maintains a high concentration and the concentration decreases in the shell, thereby having a high capacity, and since the content of nickel on the surface that is unstable at high voltage is reduced, the side reaction with the electrolyte can be minimized, thereby having stable life characteristics.
[0067] When the volume occupied by the shell is very small or the thickness of the shell is very thin, that is, when the volume ratio of the shell is less than 40 volume % or the thickness is less than 1 μm, during the heat treatment of the precursor, nickel diffuses from the core with high content to the shell, so that the nickel content of the shell increases, and the side reaction with the electrolyte is activated, resulting in unstable life characteristics.
[0068] On the other hand, when the volume occupied by the shell is large or the thickness of the shell is very thick, that is, when the volume ratio of the shell is greater than 60 volume % or the thickness is greater than 2 μm, during the process of forming the precursor, the nickel in the core diffuses into the shell with a low nickel concentration, making it impossible for the core to form a high nickel content, thereby making it difficult to achieve high capacity.
[0069] Next, the core part is described. The average particle composition of the core part can be expressed as Li(Ni a1 Mnb1 Co c1 ) 2 Here, 0.8≤a1<1. A nickel-rich positive electrode active material having a nickel content of 80 mol % or more in the core portion can be formed, so that the positive electrode active material has a high capacity.
[0070] Furthermore, the average particle composition of the shell can be expressed as Li(Ni a2 Mn b2 Co c2 )Me y O 2 Here, 0<a2≤0.8 and 0.0001≤y≤0.05. At this time, the shell portion can be composed of a lower nickel content than the core portion (a1>a2). This is to form a lower nickel content on the surface of the positive electrode active material, thereby minimizing the side reaction with the electrolyte.
[0071] Since nickel is unstable at high temperatures, it is important to have a low nickel content on the surface of the positive electrode active material. By configuring the shell portion to have a nickel content in the range of 40 mol % to 80 mol %, the side reaction between the electrolyte and nickel can be minimized, thereby enabling the positive electrode active material to have stable life characteristics.
[0072] The shell portion of the positive electrode active material is described in more detail. The shell portion of the positive electrode active material may include Me obtained from the leaching solution, wherein the Me obtained from the leaching solution may be one or more metals selected from Na, Al, Fe, Cu, Zn, Mg, Ca, B, Zr, Nb and combinations thereof.
[0073] Recently, as the interest in and use of secondary batteries has increased, recycling of waste batteries has become essential, and therefore the present invention desires that 30 mol % to 40 mol % of the positive electrode active material particles be composed of a substance obtained from a leachate recovered from waste batteries.
[0074] Specifically, in the present invention, for the leachate obtained after dissolving the internal materials of the waste battery, no additional solvent extraction step is performed. Instead, after undergoing a process of adjusting the composition of nickel, cobalt and manganese in the leachate, the shell precursor is formed from the leachate that has undergone the composition adjustment process.
[0075] The capacity retention rate of the positive electrode active material according to the present invention after 80 cycles measured in a button half-cell at 25° C. and an upper limit voltage of 4.3 V is about 95%, which is very excellent.
[0076] Next, a method for preparing a positive electrode active material according to an embodiment of the present invention is described. The method for preparing a positive electrode active material according to an embodiment of the present invention is a method for preparing a positive electrode active material including a core portion and a shell portion, comprising: a first metal-containing solution preparation step, in which a first metal-containing solution is prepared to form a core portion; a recovery solution preparation step, in which a recovery solution containing nickel, cobalt and manganese recovered from waste batteries and having a composition different from that of the first metal-containing solution is prepared to form a shell portion; a core portion precursor formation step, in which a core portion precursor is formed using the prepared first metal-containing solution; a positive electrode active material precursor formation step, in which a shell portion precursor is formed on the surface of the core portion precursor using the recovery solution, thereby forming a positive electrode active material precursor; and a positive electrode active material formation step, in which the positive electrode active material precursor is heat-treated to form a positive electrode active material.
[0077] First, the step of preparing the first metal-containing solution is described. This is a step of preparing the first metal-containing solution containing nickel, cobalt and manganese. The first metal-containing solution is a solution for forming a core precursor, wherein the content of nickel can be 70 mol% or more and less than 100 mol% relative to the total molar number of metal elements in the first metal-containing solution. That is, in order to achieve a high capacity, that is, to achieve a lithium-rich composition, the core contains nickel at a ratio of 70 mol% or more and less than 100 mol% based on the total molar number of metal elements in the first metal-containing solution for forming the core precursor.
[0078] Next, the recovery solution preparation step is described. This is a step of preparing a recovery solution containing nickel, cobalt, and manganese recovered from waste batteries and having a composition different from that of the first metal-containing solution in order to form a shell portion.
[0079] The purpose of the present invention is to recycle waste batteries. The internal materials of the waste batteries are dissolved by a wet process to obtain a leachate. At this time, the leachate can contain recycled nickel, cobalt, and manganese, and can also contain other metals and anions. The other metals can include one or more metals selected from Na, Al, Fe, Cu, Zn, Mg, Ca, B, Zr, Nb and combinations thereof, and the anions can include Cl, S, F, etc.
[0080] Furthermore, in the recovery solution preparation step, the recovery solution may be prepared by mixing the leaching solution containing nickel, cobalt and manganese recovered from the waste battery and the second metal-containing solution containing nickel, cobalt and manganese.
[0081] In the prior art, the internal materials of the discharged waste batteries are dissolved by physical and chemical treatment to obtain a leachate, and then nickel, cobalt and manganese are extracted through a solvent extraction process. However, the solvent used in the solvent extraction process is not environmentally friendly, and the additional process makes the process more complicated and time-consuming. The solvent used is expensive, resulting in a cost increase.
[0082] The present invention does not undergo such a solvent extraction step, but instead prepares a recovered solution for the synthesis of the shell precursor by mixing a second metal-containing solution that can adjust the composition of nickel, cobalt and manganese in the leachate, and uses it to form the shell precursor. The process is simplified by not undergoing a solvent extraction step, and further has a cost-saving effect by not using expensive solvents, and does not use environmentally unfriendly solvents, which also shows advantages in terms of environmental protection.
[0083] At this time, the mixing ratio of the leachate and the second metal-containing solution can be 40 mol%:60 mol% to 80 mol%:20 mol%. The contents of nickel, cobalt and manganese in the leachate are generally low for forming the shell precursor, so the recovery solution for forming the shell precursor can be prepared by mixing the leachate and the second metal-containing solution containing nickel, cobalt and manganese.
[0084] At this time, the mixing ratio of the leachate and the second metal-containing solution can be different depending on the desired shell composition and the composition of the leachate. However, when the molar percentage of the second metal-containing solution in the recovered solution is greater than 60 mol%, due to the excessive nickel content in the shell precursor, side reactions with the electrolyte are likely to occur, so there is a defect that the life stability of the positive electrode active material is reduced.
[0085] Moreover, when the molar percentage of the second metal-containing solution in the recovered solution is less than 20 mol%, the nickel content of the shell decreases due to the low content of nickel, cobalt and manganese in the recovered solution, so there is a defect of reduced capacity of the positive electrode active material.
[0086] In addition, in the recovery solution preparation step, a step of adding an alkaline solution to the leachate to adjust the pH of the leachate to 5.5 can be added. This is because the leachate obtained from the waste battery contains a variety of sulfides, which can be controlled by adjusting the pH.
[0087] More specifically, the leachate is a solution containing a variety of metal sulfides, and the metal sulfides are acidic. By adding NaOH to the leachate to increase the pH, the metal sulfides dissolved in the leachate are converted into metal hydroxides. The solubility of these metal hydroxides decreases with the increase of pH. Below pH 5.5, impurities other than nickel, cobalt and manganese can be precipitated. Therefore, by adjusting the pH, metals other than the desired precious metals (i.e., nickel, cobalt and manganese) can be precipitated, thereby controlling the impurities in the recovered solution.
[0088] Next, the core precursor forming step is described. The core precursor forming step is a step of forming the core precursor by using the first metal-containing solution. More specifically, the core precursor is formed by mixing an ammonia complexing agent and an alkaline compound in the first metal-containing solution. The ammonia complexing agent may be NH 4 OH, (NH 4 ) 2 SO 4 NH 4 NO 3 NH 4 Cl, CH 3 COONH 4 or NH 4 CO 3 etc., one of which may be used alone or as a mixture of two or more. In addition, the ammonia complexing agent may be used in the form of an aqueous solution, in which case the solvent may be water or a mixture of an organic solvent (specifically, alcohol, etc.) that can be uniformly mixed with water and water. Moreover, the ammonia complexing agent may be added at a molar ratio of 0.5 to 1 per mole of the first metal-containing solution.
[0089] In addition, the alkaline compound can be NaOH, KOH or Ca(OH) 2 The hydroxides of alkali metals or alkaline earth metals or their hydrates may be used alone or as a mixture of two or more.
[0090] The coprecipitation reaction can be carried out under an inert atmosphere such as nitrogen or argon at a temperature of 40°C to 60°C. In addition, during the coprecipitation reaction, in order to increase the reaction rate, a stirring process can be selectively performed, and the stirring speed can be 700rpm to 1500rpm. In addition, the coprecipitation reaction can be carried out under the condition of pH 10.0 to 12.0. When the coprecipitation reaction is carried out within this pH range, precursor particles can be prepared, and there will be no change in the size of the prepared precursor or particle cracking, and there will be no side reactions caused by the dissolution of metal ions from the surface of the precursor to generate various oxides.
[0091] Next, the positive active material precursor forming step is described. The positive active material precursor forming step is a step of forming a shell precursor on the surface of the core precursor using a recovered solution to form a positive active material precursor. The shell can be formed on the surface of the core precursor by the same coprecipitation reaction as the core precursor forming step described above. In this case, the coprecipitation time can be set considering the thickness of the shell precursor, the thickness of the particles of the positive active material precursor, etc.
[0092] For example, the core precursor may be coprecipitated in the recovery solution under the conditions of pH 10 to 11 and a coprecipitation time of 20 to 60 hours.
[0093] Next, the positive electrode active material formation step is described. The positive electrode active material formation step is a step of mixing and sintering the positive electrode active material precursor and the lithium-containing raw material to synthesize the positive electrode active material. The lithium-containing raw material can be a commonly used substance without special restrictions. For example, lithium-containing sulfates, nitrates, acetates, carbonates, oxalates, citrates, halides, hydroxides or oxyhydroxides can be used. As long as they are soluble in water, there are no special restrictions. Specifically, the above-mentioned lithium-containing raw material can be selected from Li 2 CO 3 、LiNO 3 、LiNO 2 、LiOH、LiOH·H 2 O, LiH, LiF, LiCl, LiBr, LiI, CH 3 COOLi, Li 2 O. Li 2 SO 4 , CH 3 COOLi and Li 3 C 6 H 5 O 7 One or a mixture of two or more.
[0094] Sintering can be performed at 730° C. to 800° C. If the sintering temperature is lower than 730° C., the discharge capacity per unit weight, cycle performance, and operating voltage may decrease due to the residue of unreacted raw materials, and if it exceeds 800° C., the discharge capacity per unit weight, cycle performance, and operating voltage may decrease due to the generation of side reactants.
[0095] The sintering step can be carried out for 13 to 20 hours in an oxidizing atmosphere such as air or oxygen or a reducing atmosphere containing nitrogen or hydrogen. By sintering under such conditions, the diffusion reaction between particles can be fully carried out, and the metal can diffuse even in the region where the internal metal concentration is constant, so that a metal oxide with a continuous metal concentration distribution from the center to the surface can be prepared.
[0096] In addition, the process may further include washing the synthesized positive electrode active material with water before the sintering step. The washing step may be performed at a temperature of 5°C to less than 10°C. By washing the positive electrode active material with water within the above temperature range, the lithium byproducts present in the positive electrode active material can be effectively removed. At this time, when the washing temperature exceeds 10°C, the positive electrode active material may be over-washed, resulting in a decrease in life characteristics and capacity characteristics.
[0097] Moreover, the method may further include a step of heat treating the positive electrode active material. The heat treatment may be performed at 600°C to 800°C for 2 to 10 hours on the washed positive electrode active material. By performing such a heat treatment process, the by-products (i.e., LiOH or Li 2 CO 3 etc.) are effectively removed, so that the positive electrode active material can be well used in lithium secondary batteries.
[0098] The present invention also provides a lithium secondary battery comprising a positive electrode active material according to the present invention. The lithium battery comprises: a positive electrode comprising a positive electrode active material having the above structure; a negative electrode comprising a negative electrode active material; and a separator located therebetween. In addition, it also comprises an electrolyte impregnated in the positive electrode, the negative electrode, and the separator. The negative electrode active material is preferably a material that can reversibly embed / de-embed lithium ions, for example, artificial graphite, natural graphite, graphitized carbon fiber, etc., and metallic lithium can also be used as a negative electrode active material. The electrolyte can be a liquid electrolyte comprising a lithium salt and a non-aqueous organic solvent, or it can be a polymer gel electrolyte.
[0099] Next, the present invention will be described in more detail by way of examples and comparative examples. However, the present invention is not limited to the examples.
[0100] <Example 1>
[0101] The first metal-containing solution used manganese sulfate hydrate (MnSO 4 .1H 2 O), nickel sulfate hydrate (NiSO 4 .6H 2 O) and cobalt sulfate hydrate (CoSO 4 .7H 2 O). Then, for manganese sulfate hydrate (MnSO 4 .1H 2 O), nickel sulfate hydrate (NiSO 4 .6H 2 O) and cobalt sulfate hydrate (CoSO 4 .7H 2 O), using distilled water as a solvent to prepare a first metal-containing solution. In addition, the first metal-containing solution is a solution for forming a core portion, and can be formed in a molar ratio of nickel, cobalt, and manganese of 90:5:5.
[0102] For the first metal-containing solution prepared in this way, 2M NaOH was used as the alkaline solution, and the molar ratio of the first metal-containing solution to NaOH (first metal aqueous solution: precipitant) was set to 1:1 to 1:2. In addition, 1M NH 4OH, and the molar ratio of the first metal-containing solution to the ammonia complexing agent is set to 1:0.5 to 1:1. The mixture of the first metal-containing solution, NaOH and the ammonia complexing agent is fed into a continuous reactor using a metering pump. Then, nitrogen is supplied to the reactor at a rate of 0.5 liters / minute to remove dissolved oxygen, and the temperature of the reactor is maintained at 50°C, while the stirring speed is adjusted to about 1000 rpm for stirring, thereby forming a core precursor.
[0103] Next, the recovered solution for forming the shell precursor is described. A leachate is obtained from a waste battery by a wet process. In the case of Example 1, the pH of the leachate is adjusted to 5.5 by adding NaOH to the leachate. Impurities other than nickel, cobalt and manganese are precipitated by adjusting the pH of the leachate to 5.5, thereby controlling the impurities of the leachate. In the leachate in which impurities other than nickel, cobalt and manganese are controlled in this way, nickel, cobalt and manganese exist in a molar ratio of 32:15:10, and a small amount of other impurities that are not removed exist.
[0104] The second metal-containing solution used manganese sulfate hydrate (MnSO 4 .1H 2 O), nickel sulfate hydrate (NiSO 4 .6H 2 O) and cobalt sulfate hydrate (CoSO 4 .7H 2 O). Manganese sulfate hydrate (MnSO 4 .1H 2 O), nickel sulfate hydrate (NiSO 4 .6H 2 O) and cobalt sulfate hydrate (CoSO 4 .7H 2 O) is further added to the leachate to prepare the molar ratio of nickel, cobalt and manganese to be 60:20:20. In addition, a small amount of other impurities from the leachate are also mixed.
[0105] Next, a process of forming a positive electrode active material precursor is performed. In order to form a shell precursor on the surface of the core precursor formed by the first metal-containing solution, the same method as the core precursor formation process is adopted, but the first metal-containing solution is replaced by the second metal-containing solution in the coprecipitation reaction, thereby forming a positive electrode active material precursor having a core-shell structure.
[0106] After mixing LiOH as a lithium salt with the positive electrode active material precursor, the mixture was heated at a temperature increase rate of 3 to 5°C / min and sintered at 750°C for 20 hours to obtain the final active material particles. The size of the final active material particles obtained was 6 to 8 μm.
[0107] <Example 2>
[0108] The first metal-containing solution used manganese sulfate hydrate (MnSO 4 .1H 2 O), nickel sulfate hydrate (NiSO 4 .6H 2 O) and cobalt sulfate hydrate (CoSO 4 .7H 2 O). In addition, for manganese sulfate hydrate (MnSO 4 .1H 2 O), nickel sulfate hydrate (NiSO 4 .6H 2 O) and cobalt sulfate hydrate (CoSO 4 .7H 2 O), using distilled water as a solvent to prepare a first metal-containing solution. In addition, the first metal-containing solution can be formed in a molar ratio of nickel, cobalt, and manganese of 90:5:5.
[0109] For the first metal-containing solution prepared in this way, 2M NaOH was used, and the molar ratio of the first metal-containing solution to NaOH (metal aqueous solution: precipitant) was set to 1:1 to 1:2. In addition, 1M NH 4 OH, and the molar ratio of the first metal-containing solution to the ammonia complexing agent is set to 1:0.5 to 1:1. The mixture of the first metal-containing solution, NaOH and the ammonia complexing agent is fed into a continuous reactor using a metering pump. Then, nitrogen is supplied to the reactor at a rate of 0.5 liters / minute to remove dissolved oxygen, and the temperature of the reactor is maintained at 50°C, while the stirring speed is adjusted to about 1000 rpm for stirring, thereby forming a core precursor.
[0110] Next, a process of preparing a recovery solution for forming a shell precursor is performed. A leachate is obtained from waste batteries by a wet process. The molar ratio of nickel, cobalt, manganese, and aluminum in the leachate is 41:12:6:7.6, and a small amount of other impurities is present. The second metal-containing solution uses manganese sulfate hydrate (MnSO 4 .1H 2 O), nickel sulfate hydrate (NiSO 4 .6H 2 O) and cobalt sulfate hydrate (CoSO 4 .7H 2 O). Then, manganese sulfate hydrate (MnSO 4 .1H 2 O), nickel sulfate hydrate (NiSO 4 .6H 2 O) and cobalt sulfate hydrate (CoSO 4 .7H 2O) is further added to the leachate to prepare the molar ratio of nickel, cobalt and manganese to be 60:20:20. In addition, a small amount of other impurities from the leachate are also mixed.
[0111] Next, a step of forming a cathode active material precursor is performed. In order to form a shell precursor on the surface of the core precursor formed from the first metal-containing solution, a coprecipitation reaction is performed using the recovered solution in the same manner to form a cathode active material precursor having a core-shell structure.
[0112] After mixing LiOH as a lithium salt with the positive electrode active material precursor, the mixture was heated at a temperature increase rate of 3 to 5°C / min and sintered at 750°C for 20 hours to obtain the final active material particles. The size of the final active material particles obtained was 5 to 6 μm.
[0113] <Comparative Example>
[0114] In the case of the comparative example, instead of using a leaching solution, a metal-containing solution having a molar ratio of nickel, cobalt, and manganese of 73:13:14 was used to form a LiNi 0.73 Co 0.13 Mn 0.14 O 2 The size of the formed positive electrode active material is 6 to 8 μm.
[0115] The positive electrode active material precursors of Example 1, Example 2 and Comparative Example were analyzed by inductively coupled plasma (ICP), and the analysis results are shown in the following table.
[0116]
Table 1
[0117]
[0118] Next, refer to Figures 1 to 6 , illustrating the SEM analysis results of Example 1, Example 2 and Comparative Example and the results of analysis by energy dispersive spectroscopy.
[0119] First, refer to Figure 1 to Figure 2 , showing the SEM analysis results of the positive electrode active material precursor particles of Example 1 and the results of the precursor particle cross section measured by energy dispersive spectroscopy. The core precursor is prepared using a first metal-containing solution with a high nickel content, and the shell precursor is prepared using a recovery solution with a relatively low nickel content, so it can be confirmed that there is the following concentration gradient: as the nickel concentration gradually decreases from the center of the positive electrode active material precursor (i.e., point 5) toward the surface of the positive electrode active material precursor (i.e., point 10 or point 1).
[0120] Moreover, for cobalt and manganese, the core precursor is prepared using a first metal-containing solution with a low cobalt and manganese content, and the shell precursor is prepared using a recovered solution with a relatively high cobalt and manganese content, so it can be confirmed that there is the following concentration gradient: the concentration of cobalt and manganese gradually increases from the center of the positive electrode active material precursor (i.e., point 5) toward the surface of the positive electrode active material precursor (i.e., point 10 or point 1).
[0121] In the case of Example 1, the pH of the leaching solution was adjusted to remove impurities. It was confirmed that, unlike the results of Example 2 to be described later, the content of impurities such as Al and Fe was very low, but a small amount of Mg that could not be removed was distributed in the core precursor and the shell precursor.
[0122] Next, refer to Figure 3 to Figure 4 , showing the SEM analysis results of the positive electrode active material precursor particles of Example 2 and the results of the precursor particle cross section measured by energy dispersive spectroscopy. The core precursor is prepared using a first metal-containing solution with a high nickel content, and the shell precursor is prepared using a recovery solution with a relatively low nickel content, so it can be confirmed that there is the following concentration gradient: as the nickel concentration gradually decreases from the center of the positive electrode active material precursor (i.e., point 5) toward the surface of the positive electrode active material precursor (i.e., point 10 or point 1).
[0123] Moreover, for cobalt and manganese, the core precursor is prepared using a first metal-containing solution with a low cobalt and manganese content, and the shell precursor is prepared using a recovered solution with a relatively high cobalt and manganese content, so it can be confirmed that there is the following concentration gradient: the concentration of cobalt and manganese gradually increases from the center of the positive electrode active material precursor (i.e., point 5) toward the surface of the positive electrode active material precursor (i.e., point 10 or point 1).
[0124] In addition, it can be confirmed that Al and Fe from the leachate are distributed in the core precursor and the shell precursor at low contents. This is because, unlike Example 1, Example 2 did not undergo a step of adjusting the pH of the leachate, so, unlike Example 1, it can be confirmed that Al and Fe are contained.
[0125] Reference Figures 5 and 6 , showing the SEM analysis results of the positive electrode active material precursor particles of the comparative example and the results of the precursor particle cross-section measured by energy dispersive spectroscopy. It can be confirmed that there is no concentration gradient as a whole, and nickel, cobalt, and manganese are uniformly distributed in the positive electrode active material precursor at a molar ratio of 73:13:14.
[0126] Next, refer to Figures 7 to 9 , shows the results of charge and discharge tests and determination of cycle characteristics of batteries using the positive electrode active materials prepared in Examples 1 and 2 and the positive electrode active materials prepared in Comparative Examples.
[0127] For the electrode, 1 mol of LiPF was dissolved in a solvent of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7. 6 A half-cell was prepared and evaluated using lithium foil as the negative electrode.
[0128] first, Figure 7 The voltage range of charge and discharge is set to 3.0-4.3V at 25°C, and charge and discharge are performed at different rates. Figure 7 The x-axis represents the number of charge and discharge cycles, and the y-axis represents the capacity.
[0129] Watch Figure 7 It can be seen that Example 1 exhibits a higher capacity than the comparative example even at a low rate of 10 C or less. Also, at a high rate of 15 C or more, it can be seen that the capacity is higher than that of the comparative example.
[0130] In the case of Example 2, at a low rate of 10C or less, the initial capacity is low due to excessive Al impurities, but at a high rate of 15C or more, it can be confirmed that a higher capacity is exhibited than that of the comparative example.
[0131] Next, Figure 8 The charge and discharge voltage range is set to 2.8-4.5V at 25°C, and the charge and discharge are performed at a rate of 1.0C. Since the Ni content on the surface of Example 1 and Example 2 is low, the unstable Ni and electrolyte side reaction at high voltage is minimized, and it can be confirmed that it has higher life characteristics than the comparative example. Looking more in detail, it can be confirmed that more capacity is preserved in Example 1 and Example 2 than in the comparative example after more than 60 cycles.
[0132] also, Fig. 9 The voltage range of charge and discharge is set to 3.0-4.3V at 45°C, and charge and discharge are performed at a rate of 1.0C. It can be confirmed that due to the high Mn content on the surface of Examples 1 and 2, thermal stability is improved, and in the high temperature evaluation at 45°C, a higher life retention rate is shown compared with the comparative example. Looking more in detail, it can be confirmed that the capacity of the comparative example cannot be maintained and drops sharply from about 40 cycles, but Examples 1 and 2 are different from the comparative example and still show stable capacity changes.
[0133] The present invention has been described above with reference to the accompanying drawings and the preferred embodiments described above, but the present invention is not limited thereto but is limited by the scope of the claims. Therefore, those skilled in the art can make various modifications and variations to the present invention without departing from the scope of the technical ideas recorded in the claims.
Claims
1. A positive electrode active material, characterized in that: include: A core portion containing a substance represented by the following chemical formula 1; as well as a shell portion surrounding the core portion and containing a substance represented by the following chemical formula 2, [Chemical formula 1] Li (Ni a1 Mr b1 Co c1 )O2 [Chemical formula 2] Li (Ni a2 Mr b2 Co c2 )Along with y O2 In Chemical Formula 1 and Chemical Formula 2, a1+b1+c1=1, a2+b2+c2+y=1, a1>a2, Me is at least one metal selected from the group consisting of Na, Al, Fe, Cu, Zn, Mg, Ca, B, Zr, Nb, and combinations thereof.
2. The positive electrode active material according to claim 1, characterized in that In Chemical Formula 1, 0.8≤a1<1, and in Chemical Formula 2, 0<a2≤0.8 and 0.0001≤y≤0.
05.
3. The positive electrode active material according to claim 1, characterized in that Nickel, cobalt, and manganese exist in a concentration gradient that gradually changes from the center to the surface of the positive electrode active material.
4. The positive electrode active material according to claim 1, characterized in that Nickel exists in a concentration gradient that gradually increases from the center to the surface of the positive electrode active material.
5. The positive electrode active material according to claim 1, characterized in that Cobalt and manganese exist in a concentration gradient that gradually decreases from the center to the surface of the positive electrode active material.
6. The positive electrode active material according to claim 1, characterized in that The average particle size of the positive electrode active material is 5 to 10 μm.
7. The positive electrode active material according to claim 1, characterized in that The average particle size of the core is 4 to 8 μm.
8. The positive electrode active material according to claim 1, characterized in that The thickness of the shell is 1 to 2 μm.
9. The positive electrode active material according to claim 1, characterized in that The volume of the shell portion is 40 to 60 volume % based on 100 volume % of the total volume of the positive electrode active material including the core portion and the shell portion.
10. The positive electrode active material according to claim 1, characterized in that Me comes from the leachate of waste batteries.
11. The positive electrode active material according to claim 1, characterized in that The capacity retention rate of the positive electrode active material after 80 cycles measured at 25° C. and an upper limit voltage of 4.3 V in a button half cell is 91% or more.
12. A method for preparing a positive electrode active material, which is a method for preparing a positive electrode active material comprising a core portion and a shell portion, characterized in that: include: A first metal-containing solution preparation step of preparing a first metal-containing solution for forming a core portion; a recovery solution preparation step, in order to form the shell portion, preparing a recovery solution recovered from waste batteries containing nickel, cobalt and manganese and having a composition different from that of the first metal-containing solution; a core precursor forming step, using the prepared first metal-containing solution to form a core precursor; a positive electrode active material precursor forming step, using the recovered solution to form a shell precursor on the surface of the core precursor, thereby forming a positive electrode active material precursor; as well as In the positive electrode active material forming step, the positive electrode active material precursor is heat-treated to form the positive electrode active material.
13. The method for preparing a positive electrode active material according to claim 12, characterized in that: In the first metal-containing solution preparation step, the first metal-containing solution contains 70 to 100 mol % of nickel based on 100 mol % of the total metal elements contained in the first metal-containing solution.
14. The method for preparing a positive electrode active material according to claim 12, characterized in that: In the recovery solution preparation step, the leaching solution containing nickel, cobalt and manganese recovered from the waste battery and the second metal-containing solution containing nickel, cobalt and manganese are mixed to prepare a recovery solution.
15. The method for preparing a positive electrode active material according to claim 14, characterized in that: The mixing ratio of the leaching solution and the second metal-containing solution is 40 mol %:60 mol % to 80 mol %:20 mol %.
16. The method for preparing a positive electrode active material according to claim 12, characterized in that: In the recovery solution preparation step, an alkaline solution is mixed with a leachate containing nickel, cobalt and manganese recovered from waste batteries to adjust the pH of the leachate to 5.5 or less.
17. The method for preparing a positive electrode active material according to claim 12, characterized in that: In the core precursor forming step, the prepared first metal-containing solution and the ammonia complexing agent are mixed at a molar ratio of 1:0.5 to 1:1 to a pH of 10 to 12, and stirred at a temperature of 40 to 60° C. and a speed of 700 to 1500 rpm in a nitrogen atmosphere to form a core precursor.
18. The method for preparing a positive electrode active material according to claim 12, characterized in that: In the positive electrode active material precursor forming step, the core precursor is coprecipitated in the recovery solution under the conditions of pH 10 to 11 and coprecipitation time 20 to 60 hours to form the shell precursor.
19. The method for preparing a positive electrode active material according to claim 12, characterized in that: The positive electrode active material forming step includes a process of mixing a positive electrode active material precursor and a lithium-containing raw material and then sintering the mixture at 750 to 850° C. for 13 to 20 hours.
20. The method for preparing a positive electrode active material according to claim 19, characterized in that: Before the sintering step, the positive electrode active material precursor is washed with water at a temperature of 5° C. or higher and lower than 10° C.
Citation Information
Patent Citations
Hybrid solar collector
KR1020110122544A